Português Physiological performance and productivity of Tahiti lime under irrigation and rootstocks in the Amazon - Caravina, Sandro Marcelo; Holanda, Lucas Almeida de; Roncatto, Givanildo; Duarte Santos, Emily Carolina; Silva, Igor Eli da Silva; Silva, Adinan Alves da; Costa, Alan Carlos da (Comunicata Scientiae, 2025)
The aim of this research was to study the physiological and productive performance of five rootstocks cultivated in the lemon ‘Tahiti CNPMF–02’ under irrigated and non-irrigated conditions in the Amazon in the sixth year of dense planting. In a completely randomized design, in a 2x5 factorial scheme (irrigation x rootstock) evaluated in the dry and rainy season, applied to the rootstocks citrumelo 'Swingle' (CTSW), lemon tree 'Cravo Santa Cruz' (LCSC), citrandarim 'San Diego'(CTDI), and 2 hybrids crossing tangerine 'Sunki Tropical' and Poncirus trifoliata ‘Flying Dragon’ called TSKCxTRFD-003 (003), TSKCxTRFD–006 (006), being evaluated water relations, gas exchange, chlorophyll fluorescence, among other physiological characteristics and also the production components were. Rootstock 006 has a more efficient physiological metabolism, with and without irrigation in the face of water deficit, being more productive in the Amazon. Rootstock 003, although with good metabolic performance and adequate plant architecture, even under water deficit conditions, did not demonstrate changes in productivity. The CTDI rootstock, even when irrigated, did not demonstrate gains in productivity in the dry season, even with efficient physiological mechanisms of drought tolerance. The LCSC rootstock has less tolerance to water deficit, and even under irrigation in the dry season, it does not show improvements in its performance. However, this rootstock has high productivity in the rainy season regardless of irrigation. The CTSW rootstock must be used in restricted plantings only in management that can be irrigated, associated with annual crown adjustment pruning, avoiding densification without densification and mandatory annual crown adjustment pruning.